NMR study on reaction processes from aluminum chloride hydroxides to alpha alumina powders. Issue 5 (8th October 2018) - Nýblová, Daniela; Senna, Mamoru; Düvel, Andre; Heitjans, Paul; Billik, Peter; Filo, Juraj; Šepelák, Vladimír
Abstract: Starting from gelatinous aluminum chloride hydroxide, the transformation process toward α‐Al2 O3 was examined using 27 Al NMR, both in the liquid and solid states, as a main analytical tool. By increasing the hydrolysis ratio ( h, defined as [OH − ]/[Al 3+ ]) of the starting aqueous precursor up to h = 2.5, the transition temperature to the final product, α‐Al2 O3, decreased to as low as 500°C. In this case, the structural change from amorphous alumina to α‐Al2 O3 took place without intermediate transition Al2 O3 phases. Examining the process of networking during the transition from aqueous sol–through the state of xerogel–to final anhydrous oxide by nuclear magnetic resonance (NMR) revealed the presence of highly polymeric species mainly ascribed to δ‐[Al2 O8 Al28 (OH)56 (H2 O)24 ] 18+ (δ‐Al30 ). δ‐Al30 species were found in the solution phase and became predominant after drying. We conclude that the lower temperature synthesis of α‐Al2 O3 became possible due to preformation of polymerized AlO6 construction units in the precursor, reducing the energy barrier for the nucleation of the final α‐Al2 O3 phase. Abstract : Low temperature synthesis of α?Al2 O3 from gelatinous aluminum chloride hydroxide containing highly polymeric Al species tracked by 27 Al NMR.